An online survey of perspectives towards the impact of the covid-19 pandemic amongst caregivers of adolescents with ASD - Nadlada Tawankanjanachot; Craig Melville; Maria Truesdale; Lisa Kidd (BMC, 2024)
Abstract Background The coronavirus disease (COVID-19) pandemic has had a negative impact on the health and mental health of adolescents and adolescents with autism spectrum disorders (ASD) and their caregivers, have been disproportionally affected. The purpose of this study was to investigate the impact of COVID-19 on Thai caregivers and adolescents with ASD. Methods This study used an online survey with closed and free text questions to investigate how the pandemic had impacted on social skills development and psychological variables, and perceived needs for support. The survey link was shared to parents via the Yuwaprasart Withayopathum Child and Adolescent Hospital and the social media platforms of known ASD stakeholder networks in Thailand. Binary logistic regression was used to investigate the relationships between sociodemographic characteristics, service use, and social skills problems experienced by adolescents during the pandemic. Content analysis was applied to analyse free-text data. Results A total of 376 caregivers of adolescents with ASD aged 10-19 years completed the survey, of which 364 were included in the analysis. In total, 38.7% of caregivers reported that during the pandemic the social skills of their adolescent family member had worsened. Most families reported that they were able to continue to access support from healthcare and educational services, albeit in different ways than pre-pandemic, during the acute stages of the pandemic which benefited the maintenance of ASD symptoms and social skills. Factors identified as reducing the odds of a worsening in social skills during the pandemic included; regular access to treatment for adolescents (odds ratio [OR] = 0.55, confidence interval 95% (CI) 0.32-0.98, p = 0.044), caregivers feeling that they had sufficient support from hospitals (OR = 0.46, 95% CI 0.26-0.81, p = 0.007) and older age of adolescents (OR = 0.53, CI 0.29-0.99, p = 0.047). The qualitative free text comments showed that the caregivers felt that greater information on managing adolescent behaviours, opportunities for adolescents to practice social skills, and the provision of greater emotional support and material assistance from healthcare professionals during the pandemic would have helped them to care for the adolescents with ASD. Conclusion Regular access to services, support from hospitals during the pandemic and older age in adolescence may have helped prevent the worsening of the social skills problems of adolescents with ASD.